Investigation on blood plasma and hair copper levels in clinically healthy cattle in Elazig and it's vicinity - Çimtay, I; Ölçücü, A (Scientific Technical Research Council Turkey, 2000)
The objective of this study was to determine blood plasma and hair copper levels in clinicially healthy Swiss Brown and Holstein cows. This study was performed on SO cows, 3-6 years old. Blood and hair samples were collected in December, March, June and September. Mean plasma copper levels in December, March, June and September were 68.23+/-2.62 44.58+/-1.78, 52.79+/-2.15 and 52.76+/-2.59 mu g/dl respectively. Also mean hair copper levels were 5.78+/-0.22. 5.45+/-0.15, 5.25+/-0.11 and 5.77+/-0.15 ppm respectively. The levels of plasma and hair copper showed great differences in regard to the months of study and races, but there were no significant differences associated with gestation and lactation factors. Mean plasma copper levels in March, June and September (44.58+/-1.78. 52.79+/-2.15 and 52.76+/-2.59 mu g/dl respectively) and mean hair copper levels in March and June (5.45+/-0.15 and 5.25+/-0.11 ppm respectively) were lower than the accepted critical levels for subclinical copper deficiency.
Keywords: cow; blood plasma; hair; copper